The Concept Of Self As Moderator Between Self-Esteem And Trend Towards Others - Rus Mihaela; Sandu Mihaela Luminița; Senouci Boumediene; Tasențe Tănase; Djellouli Zineb (Technium Social Sciences Journal, 2020)
The study aimed to determine the concept of self as moderator between self-esteem and trend towards others.. The study sample consists of (300) student who chosen from two countries, and to achieve the objectives of the study the researchers use self-esteem scale, self concept scale, trend toward others scale, after collecting and processing information statistically using the Statistical Package for Social Sciences SPSS, the researchers reached the following results: the level of self concept at university students is low. the level of self-esteem at university student is medium. the level of trend toward others at university student is medium. the self concept don’t play moderator role between self-esteem and trend toward others. It is assumed that there are significant differences in terms of self-esteem compared to Romania Algeria. It is assumed that there are significant differences in the comparative self concept of Romania Algeria.